2016
DOI: 10.1186/s13007-016-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

A rapid approach to investigate spatiotemporal distribution of phytohormones in rice

Abstract: BackgroundPhytohormones play crucial roles in almost all stages of plant growth and development. Accurate and simultaneous determination of multiple phytohormones enabled us to better understand the physiological functions and the regulatory networks of phytohormones. However, simultaneous determination of multiple phytohormones in plant is still a challenge due to their low concentrations, structural and chemical diversity, and complex matrix of plant tissues. Therefore, development of a simple and selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Liquid chromatography coupled with mass spectrometry (LC-MS) [117,[132][133][134][135] has become much more widely used because of its high capacity to separate and detect plant hormones without derivatization but with high sensitivity and efficiency [71]. Ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) is now one of the most common approaches for quantification of auxins and their conjugates [136][137][138][139][140], often employing triple quadrupole mass spectrometers that improve specificity and reduce detection limits [136][137][138][139]. Recent improvements in GC-MS/MS and LC-MS/MS techniques for auxin analysis have been the focus of comprehensive reviews [9,135].…”
Section: Chromatography and Mass Spectrometrymentioning
confidence: 99%
“…Liquid chromatography coupled with mass spectrometry (LC-MS) [117,[132][133][134][135] has become much more widely used because of its high capacity to separate and detect plant hormones without derivatization but with high sensitivity and efficiency [71]. Ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) is now one of the most common approaches for quantification of auxins and their conjugates [136][137][138][139][140], often employing triple quadrupole mass spectrometers that improve specificity and reduce detection limits [136][137][138][139]. Recent improvements in GC-MS/MS and LC-MS/MS techniques for auxin analysis have been the focus of comprehensive reviews [9,135].…”
Section: Chromatography and Mass Spectrometrymentioning
confidence: 99%
“…To date, MS studies have identified many plant hormones and their metabolites that might be involved in the molecular mechanisms and physiological functions of plant development, but the analysis at unicellular level has remained a challenge. Several large-scale studies on plant hormone have been reported, these studies have promoted our understanding on the dynamic spatial-temporal distribution of plant hormone [19,35,77]. Current sample pretreatment methods for plant hormone is expected to be further optimized for realizing the in situ, real-time and high spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…1) [62]. Cai et al [77] developed a clean-up strategy employing a single-step dispersive solid-phase extraction (DSPE) combined with UPLC-MS/MS to obtain spatialtemporal information of 54 plant hormones including auxins, ABA, SA, JA, GAs and CKs. Wang et al [75] used a combination of EME and LC-MS/MS to quantitatively detect six acidic plant hormones in 20 mg citrus leaf sample with a limit of detection (LOD) ranging from 0.1 to 10 ng mL −1 .…”
Section: Common Pretreatment Methods In Plant Hormone Analysismentioning
confidence: 99%
“…Just a small number of GAs have intrinsic biological activity, and they regulate many aspects of growth and development throughout the plant life cycle, from seed germination and vegetative growth to reproductive growth (Swain et al ., ; Eriksson et al ., ; Gomez et al ., ; Racca et al ., ). The level and distribution of GAs in plant tissues are dynamically changing with different plant growth and development stages as well as external living environments (Vettakkorumakankav et al ., ; Cai et al ., ). To gain a deep insight into their physiological functions and action mechanisms, it is crucial to know the precise location of endogenous GAs and their local concentrations (Novak et al ., ).…”
Section: Introductionmentioning
confidence: 97%